PENGARUH KONSENTRASI DAN LAMA DERAAN ETANOL PADA VIABILITAS BENIH CAISIN (Brassica rapa L. cv. grup Caisin) - Jumawati, Riana; Wahyuni, Ari; Putri, Ria; Paulina, Maria (Jurnal Agroteknologi dan Pertanian (JURAGAN), 2021)
Mustard greens (Brassica rapa L.) is a vegetable crop that is widely consumed by Indonesians. The use of quality seeds can increase productivity. The quality of seeds can decrease during the storage period. The process of quality degradation is a natural and unavoidable process. One method of artificially fast aging of the seeds is by electrocuting the seeds using chemicals. Depression of seeds with alcohol can be used to test the deterioration of seeds due to poisoning caused by alcohol. This study aims to influence the ethanol / alcohol concentration and the duration of agitation on the viability of caisin seeds. This study used a factorial treatment design (2x5) in a completely randomized design (CRD) with four replications. The first factor is the concentration of ethanol (20% and 25%) and the second factor is the duration of the stroke (30, 60, 90, 120, and 150 minutes). The results showed that the ethanol concentration and the calming time had a significant effect on the viability of the caisin seeds. The viability of caisin seeds decreased to 45.5% with ethanol pressure for 150 minutes at a concentration of 20%.